2013
DOI: 10.3329/jhpn.v30i4.13326
|View full text |Cite
|
Sign up to set email alerts
|

Iodized Salt Consumption in Sudan: Present Status and Future Directions

Abstract: Iodine Deficiency Disorders (IDD) Control Programme in Sudan adopted salt iodization as the long-term strategy in 1994. In 2000, it was found that less than 1% of households were using adequately-iodized salt. The objectives of this study were to: (i) study the coverage and variation of different geographical regions of Sudan regarding access to and use of iodized salt, (ii) explore the possible factors which influence the use of iodized salt, (iii) develop recommendations to help in the implementation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 7 publications
4
16
2
Order By: Relevance
“…The result of this study is higher than the findings observed in different parts of Ethiopia: Hawassa town 0% [18], Shebe town, south west Ethiopia 19% [19], Northern Ethiopia 25% [20], Gondar 29% [10], JigJiga town, Eastern Ethiopia 26.6% [21], and Laelay Maychew District, Northern Ethiopia 33% [22] of the households have access to iodized salt. The finding from the current study is also higher than the findings observed in Sudan 14.4% [9] and Sindh and Punjab provinces of Pakistan 15% [8]. The improvement observed in the current study might be attributed to the application of more effective strategies in the production and distribution of iodized salt to enhance universal salt iodization program by the Ethiopian Ministry of Health in general and zonal health department in particular.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…The result of this study is higher than the findings observed in different parts of Ethiopia: Hawassa town 0% [18], Shebe town, south west Ethiopia 19% [19], Northern Ethiopia 25% [20], Gondar 29% [10], JigJiga town, Eastern Ethiopia 26.6% [21], and Laelay Maychew District, Northern Ethiopia 33% [22] of the households have access to iodized salt. The finding from the current study is also higher than the findings observed in Sudan 14.4% [9] and Sindh and Punjab provinces of Pakistan 15% [8]. The improvement observed in the current study might be attributed to the application of more effective strategies in the production and distribution of iodized salt to enhance universal salt iodization program by the Ethiopian Ministry of Health in general and zonal health department in particular.…”
Section: Discussioncontrasting
confidence: 68%
“…Other similar studies elsewhere reported the presence of an association between urban and the presence of adequately iodized salt at home [7–9, 11]. The reason may be that those who were unaware of its significance are the socially and economically disadvantaged rural population.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A 2013 publication described Sudan as having ‘made insufficient progress to achieve Millenium Development Goal 4 and having levels of child and infant mortality that are among the highest in the region and the world’ 58. The current infant mortality rate is 60 per 1000 live births and the under-5-year mortality rate is 82 deaths per 1000 live births 58 59. The neonatal mortality rate is also high, ranging from 34 to 47 per 1000 births59 with a maternal mortality rate of 311 deaths/100 000 live births 58.…”
Section: Maternal and Child Healthmentioning
confidence: 99%
“…In India, Malhotra et al [9] revealed that, religion, education of spouse of head of family, occupation and education of the family head, per capita monthly income, source of salt and quantum of salt bought at one time were not strongly linked (associated) with the use of adequately iodised salt. Also is being found by Mahfouz et al [10] that, getting iodised salt in the market or staying in an urban area by household head, having a more educated, a male and comparatively wealthy household head increased the probability of utilising iodised salt among households in Sudan. Further in Pakistan (Punjab and Sindh), people in the Province of Punjab and rural dwellers were found by Khan et al [11] to be less likely to use iodised salt.…”
mentioning
confidence: 97%